2020
DOI: 10.1093/ehjci/jeaa256
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implication of CT-FFR based functional SYNTAX score in patients withde novothree-vessel disease

Abstract: Aims This study was aimed at investigating whether a machine learning (ML)-based coronary computed tomographic angiography (CCTA) derived fractional flow reserve (CT-FFR) SYNTAX score (SS), ‘Functional SYNTAX score’ (FSSCTA), would predict clinical outcome in patients with three-vessel coronary artery disease (CAD). Methods and results The SS based on CCTA (SSCTA) and ICA (SSICA) were retrospectively collected in 227 consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
3
15
0
Order By: Relevance
“…Multiple studies confirmed CT-FFR is a better predictor of MACEs in patients with CAD, especially for patients with intermediate-range or severe-range coronary stenosis (≥ 50%). Moreover, patients with CT-FFR ≤ 0.80 had a higher risk of MACEs than patients with CT-FFR > 0.80 [ 5 , 11 , 24 , 25 ], which was consistent with our study. We suspected that CT-FFR can provide high sensitivity and specificity to identify myocardial ischemia, CT-FFR ≤ 0.80 can indicate functional ischemia, while myocardial ischemia was associated with a trend towards an increase in MACEs risk.…”
Section: Discussionsupporting
confidence: 92%
“…Multiple studies confirmed CT-FFR is a better predictor of MACEs in patients with CAD, especially for patients with intermediate-range or severe-range coronary stenosis (≥ 50%). Moreover, patients with CT-FFR ≤ 0.80 had a higher risk of MACEs than patients with CT-FFR > 0.80 [ 5 , 11 , 24 , 25 ], which was consistent with our study. We suspected that CT-FFR can provide high sensitivity and specificity to identify myocardial ischemia, CT-FFR ≤ 0.80 can indicate functional ischemia, while myocardial ischemia was associated with a trend towards an increase in MACEs risk.…”
Section: Discussionsupporting
confidence: 92%
“…In comparison to CCTA-SS, FFRct better predicts MACE, improves diagnostic accuracy, and the calculated value of FFRct is similar to the functional SYNTAX score [58,59] . Another study confirmed that non-invasive FFRct was significantly associated with invasive FFR at the same time (FFRct AUC: 0.90, 95%CI: 0.87-0.94) [60] , and it can be used in the risk stratification assessment of cardiac surgery.…”
Section: Non-invasive Syntax Score and Syntax Score ⅲmentioning
confidence: 80%
“…Both preoperative conditions and perioperative therapies are determining factors of the clinical outcomes for CABG patients [ 15 ]. Therefore, the EuroSCORE system was established for estimating the impact of preoperative complications, whereas the syntax scoring system is used for estimating the impact and severity of coronary artery stenosis [ 16 , 17 ]. Anti-infection treatments are an important and common therapy during the post-operative period, and CABG patients are no exception.…”
Section: Discussionmentioning
confidence: 99%
“…EuroSCORE is a tool for predicting CABG outcomes [ 16 ]. The covariables of the present analysis were selected based on the EuroSCORE.…”
Section: Discussionmentioning
confidence: 99%